A Pediatric Case of Cowden Syndrome with Graves' Disease. (31st January 2017) - Patraquim, Cláudia; Fernandes, Vera; Martins, Sofia; Antunes, Ana; Marques, Olinda; Carvalho, José Luís; Correia-Pinto, Jorge; Meireles, Carla; Ferreira, Ana Margarida
Abstract : Cowden syndrome (CS) is a rare dominantly inherited multisystem disorder, characterized by an extraordinary malignant potential. In 80% of cases, the human tumor suppressor gene phosphatase and tensin homolog (PTEN) is mutated. We present a case of a 17-year-old boy with genetically confirmed CS and Graves' disease (GD). At the age of 15, he presented with intention tremor, palpitations, and marked anxiety. On examination, he had macrocephaly, coarse facies, slight prognathism, facial trichilemmomas, abdominal keratoses, leg hemangioma, and a diffusely enlarged thyroid gland. He started antithyroid drug (ATD) therapy with methimazole and, after a 2-year treatment period without achieving a remission status, a total thyroidectomy was performed. Diagnosis and management of CS should be multidisciplinary. Thyroid disease is frequent, but its management has yet to be fully defined. The authors present a case report of a pediatric patient with CS and GD and discuss treatment options.